Nurses' perception on medication administration error (MAE) at surgical wards in HUSM - Sukeri, Aizatul Shakira Ahmad (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2011)
Mortality rate due to medication error incidence in United States was higher than incidence of motor vehicle accidents, breast cancer or AIDS. Although many preventative measures were implemented to reduce the incidence, the incidence is still alarming particularly related to violation of 5Rights during drug administration. As medication administration is one of the vital roles of nurses, it was crucial to determine nurses' perception towards medication administration error (MAE) at the busiest wards in a teaching hospital. This descriptive study aimed to determine the nurses' perception on medication administration error at various surgical wards in Hospital Universiti Sains Malaysia (HUSM). Seventy one nurses from various surgical wards were selected for this study by using stratified sampling method. Data was collected by using self administered questionnaire adapted from Demehin, Babalola and Erhun, (2008) and Wilkins and Shields, (2008). Using SPSS version 18, analysis of data was conducted using descriptive and One-Way ANOVA. All nurses (100%) had awareness on MAE. In addition, 26.80% of the nurses perceived the estimated frequency of MAE occurrence was at 1 per 10 drug administration. Most of the nurses perceived wrong time (22.54%), wrong drug (20.80%) and wrong doses (20.80%) as the most frequently occurring type of MAE. The nurses also perceived that distraction and interruption during medication administration process (17.32%), excess workload (14.70%), medication named was quite similar (14.17%), and wrong labeling (e.g. medicine, patient name) as the main factors contributing to MAE. Measures to reduce MAE incidence were encouraging self reporting of medication administration error (14.75%), avoidances of all forms distractions (14.53%), importance of continuous professional education and re-training of all nurses in the right way of administering medication (13.67%) and involvement and cooperation in medication delivery by all health care delivery (e.g. nurses, pharmacists and physicians) (13.45%). A One-Way ANOVA showed that there was a significant difference in nurses' perception towards role overload between three surgical wards, F(2, 68) = 4.109, p = 0.021. All surgical nurses had awareness of MAE incidence with the main contributing factor related to the procedure during drug administration and nurses' perception towards role overload in different surgical ward. The information obtained from this study brings to light important to apply measures and guideline for nurses in reducing the incidence of MAE.